Adaptive trans‐generational phenotypic plasticity and the lack of an experimental control in reciprocal match/mismatch experiments. Issue 12 (25th August 2016) - Engqvist, Leif; Reinhold, Klaus
Summary: Parental information about the prevailing environmental condition may enable offspring to adjust their phenotypes in accordance with future demands. The state‐of‐the‐art experimental test of the occurrence of such adaptive trans‐generational phenotypic plasticity is a 'match/mismatch' approach: a fully factorial reciprocal transplant experiment where offspring encounter environments either matching or mismatching parents' experience. Here, we highlight that a hidden assumption of this approach is that the effect of early and late offspring environment acts completely additively on offspring fitness. Likely violations of this assumption, such that early 'silver‐spoon' effects are more valuable when later environmental conditions are relatively harsh, will bias the estimates of potential trans‐generational effects. We discuss the different implications of this on the interpretation of the outcome of match/mismatch experiments and suggest different complementary and alternative approaches.